Sleeping difficulties and health‐related quality of life in Parkinson's disease. (10th June 2016) - Ylikoski, A.; Martikainen, K.; Sieminski, M.; Partinen, M.
Abstract : Objective: Various sleep‐related symptoms occur in Parkinson's disease (PD). Their occurrence with health‐related quality of life (HRQL), comorbid sleep disorders, and other comorbidities was studied. Methods: Altogether, 1447 randomly selected patients with Parkinson's disease, aged 43–89 years, participated in a questionnaire study. A structured questionnaire with 207 items was based on the Basic Nordic Sleep Questionnaire. Questions on demographics, PD, sleep disorders, and comorbidities were included. Results: The response rate was 59.0%, and of these, 80% had answered to all questions that were used in the analyses (N=684). Occurrence of long sleep was found in 26.2% of the subjects, short sleep in 32.5%, poor sleep in 21.2%, sleep deprivation in 33.8%, disrupted sleep in 47.4%, and difficulties to fall asleep in 12.2%, respectively. Poor self‐rated health and poor quality of life occurred in 44.4% and in 43.3% of all participants. In the logistic regression, age and gender differentially predicted long sleep and sleep deprivation, such that older age and being male were positively associated with long sleep but negatively associated with the report of sleep deprivation. Depression, subjective negative stress, and fatigue occurred with long sleep. On the other hand, poor sleep and excessive daytime sleepiness occurred with short sleep and sleep deprivation. Conclusions: The sleep difficulties in PD are frequent. The long sleeping patients have depression, stress, and fatigue.